Copy Number Variation Identification on 3,800 Alzheimer’s Disease Whole Genome Sequencing Data from the Alzheimer’s Disease Sequencing Project - Lee, Wan-Ping; Tucci, Albert A.; Conery, Mitchell; Leung, Yuk Yee; Kuzma, Amanda B.; Valladares, Otto; Chou, Yi-Fan; Lu, Wenbin; Wang, Li-San; Schellenberg, Gerard D.; Tzeng, Jung-Ying (Frontiers in Genetics, 2021)
Alzheimer’s Disease (AD) is a progressive neurologic disease and the most common form of dementia. While the causes of AD are not completely understood, genetics plays a key role in the etiology of AD, and thus finding genetic factors holds the potential to uncover novel AD mechanisms. For this study, we focus on copy number variation (CNV) detection and burden analysis. Leveraging whole-genome sequence (WGS) data released by Alzheimer’s Disease Sequencing Project (ADSP), we developed a scalable bioinformatics pipeline to identify CNVs. This pipeline was applied to 1,737 AD cases and 2,063 cognitively normal controls. As a result, we observed 237,306 and 42,767 deletions and duplications, respectively, with an average of 2,255 deletions and 1,820 duplications per subject. The CNVs we identified tended to be more abundant and longer in AD cases compared to cognitively normal, elder controls.